2012
DOI: 10.1155/2012/542402
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Best Criteria to Determine Final and Initial Speeds within Ramp Exercise Testing Protocols

Abstract: This study compared strategies to define final and initial speeds for designing ramp protocols. V O2max  was directly assessed in 117 subjects (29 ± 8 yrs) and estimated by three nonexercise models: (1) Veterans Specific Activity Questionnaire (VSAQ); (2) Rating of Perceived Capacity (RPC); (3) Questionnaire of Cardiorespiratory Fitness (CRF). Thirty seven subjects (30 ± 9 yrs) performed three additional tests with initial speeds corresponding to 50% of estimated V O2max  and 50% and 60% of measured V O2max . … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
33
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 36 publications
0
33
0
1
Order By: Relevance
“…However, the accuracy of VO 2max assessment depends on the characteristics of the test protocol employed [5,13]. Previous studies [5,7,23] have shown that a ramp exercise protocol seems to be a better approach to assessing VO 2max than traditional step-incremented protocols. This is because the ramp protocol incorporates small constant work rate increments that induce more uniform hemodynamic and respiratory responses, and can be individualized to elicit a test duration that is conducive to accurate VO 2max determination [23].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, the accuracy of VO 2max assessment depends on the characteristics of the test protocol employed [5,13]. Previous studies [5,7,23] have shown that a ramp exercise protocol seems to be a better approach to assessing VO 2max than traditional step-incremented protocols. This is because the ramp protocol incorporates small constant work rate increments that induce more uniform hemodynamic and respiratory responses, and can be individualized to elicit a test duration that is conducive to accurate VO 2max determination [23].…”
mentioning
confidence: 99%
“…In a later study, these investigators [22] validated the VSAQ by directly assessing VO 2max in a larger sample (n = 337). Nevertheless, findings of previous studies show only a moderate relationship between measured and predicted VO 2max using the VSAQ to determine the final work rate within ramp protocols in healthy (r = 0.33 to 0.50) [7,12] and well-conditioned populations (r = 0.47) [13]. Another non-exercise model for estimating VO 2max is the Questionnaire of Cardiorespiratory Fitness -CRF [16].…”
mentioning
confidence: 99%
“…1−3 The VSAQ has a good intra-(ICC of 0.88; 95% CI of 0.76 to 0.94) and inter-rater reliability (ICC of 0.90; 95% CI of 0.80 to 0.95). 4 Both VSAQ (VO 2peak, ICC of 0.57, standard errors of estimate 7.63 mL/kg/min, P < .0001) and the DASI (VO 2peak , spearman correlation coefficient of 0.81) correlate moderate to good with aerobic capacity. 1,5 Functional Mobility Functional mobility was measured using the timed upand-go (TUG) test (in s), two-minute walk test (2MWT, in m), and the five times sit-to-stand (FTSTS) test (in s).…”
Section: Description Of the Examination Strategy Of The Physical Thermentioning
confidence: 88%
“…In case the ventilatory threshold was not reached within the submaximal test, the procedure continued with increments of ~25-30 watts. The data to estimate the initial load of maximal graded exercise tests (GXTs) was planned to be completed within 8-12 min (da Silva et al, 2012; Myers et al, 1991). Maximal GXTs were then performed to determine VO 2peak of the participants.…”
Section: Methodsmentioning
confidence: 99%